2022
DOI: 10.3389/fcimb.2021.799276
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Proinflammatory Cytokine Production and Immunometabolic Impairment of NK Cells Exposed to Mycobacterium tuberculosis and Cigarette Smoke

Abstract: AimSmoker COPD patients with chest radiological signs of prior tuberculosis (TB) showed more severe lung damage, but the mechanisms remain unclear. Emerging evidence has implicated NK cells in the pathogenesis of both COPD and TB. The purpose of this study was to delineate the profile and cytokine production of NK-cell subpopulations and their immunometabolic changes after exposure to both cigarette smoke (CS) and Mycobacterium tuberculosis(MTB).MethodsWe profiled NK-cell subpopulations in terms of percentage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…Our previous study showed that Mtb infection promoted cigarette smoke-exposed macrophages to polarise toward both M1 and M2 phenotypes, along with enhanced production of MMP9 and MMP12 27. In an earlier study, we reported increased cytokine production and impaired cell metabolism in natural killer cells after coexposure to cigarette smoke and purified protein derivative 29 30…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our previous study showed that Mtb infection promoted cigarette smoke-exposed macrophages to polarise toward both M1 and M2 phenotypes, along with enhanced production of MMP9 and MMP12 27. In an earlier study, we reported increased cytokine production and impaired cell metabolism in natural killer cells after coexposure to cigarette smoke and purified protein derivative 29 30…”
Section: Discussionmentioning
confidence: 96%
“… 27 In an earlier study, we reported increased cytokine production and impaired cell metabolism in natural killer cells after coexposure to cigarette smoke and purified protein derivative. 29 30 …”
Section: Discussionmentioning
confidence: 99%
“… 49 Although the exact mechanism of defective response of NK cells remains unclear, at present, evidence indicates that MTB may hijack the host gene expression to inhibit the immuno-metabolic reprogramming of NK cells. 50 , 51 Importantly, this immunosuppressed status could not be reversed by cytokine-mediated activation. Further study is urgently required to elucidate the molecular mechanism involved in impaired IFN-γ production capability of NK cells in TB patients.…”
Section: Discussionmentioning
confidence: 99%
“…NK cells are important innate immune effectors, and their abnormal activation can lead to tissue injury and chronic inflammation [48]. CS exposure may aggravate the injury of lung epithelial cells by increasing the cytotoxicity and cytokine production of NK cells [49]. Overall, the M2 macrophages and the activated NK cells play a pivotal role in airway inflammation and lung parenchyma destruction.…”
Section: Discussionmentioning
confidence: 99%